Multidimensional Analysis of Head Teachers’ Attitudes, Beliefs, Leadership Practices, and Perceived Barriers towards Inclusive Education in Gilgit-Baltistan - Haideri, Muhammad Hadi; Dr. Zahida Parveen, (JIE, 2025)
Inclusive education is vital for ensuring equitable access to quality education, particularly in resource-limited regions like Gilgit-Baltistan, Pakistan, where socio-cultural and infrastructural challenges persist. Head teachers play a pivotal role in shaping inclusive school environments through their attitudes, beliefs, and leadership practices. This study examines the multidimensional factors influencing inclusive education in Gilgit-Baltistan, Pakistan, focusing on primary school head teachers' attitudes, beliefs, leadership practices, and perceived barriers. Grounded in the Theory of Planned Behavior and transformative leadership frameworks, the research addresses the unique challenges of this culturally diverse region. Using a quantitative descriptive design, data were collected from 138 head teachers across six districts (Gilgit, Ghizer, Skardu, Ghanche, Diamer, and Astore) via a validated Likert-scale questionnaire. Descriptive and inferential statistics (t-tests, ANOVA) revealed moderately positive attitudes toward inclusion's social benefits (M=3.14–3.45), strong beliefs in teacher training and incentives (M=3.27–3.57), supportive leadership in policy alignment and stakeholder engagement (M=2.91–3.32), but significant barriers including insufficient training, overcrowding, and financial constraints (M=4.17–4.38). Gender differences favored females in attitudes, beliefs, and leadership (p<.001), while district variations highlighted disparities between urban (Gilgit, Skardu) and rural areas (Ghizer, Ghanche, Diamer, Astore). Findings inform targeted interventions to advance equitable education. Key words: Inclusive education, Head teachers, Gilgit-Baltistan, Leadership practices, Barriers to education